The Execution Of Additional Sanction In The Form Of Repair Due To Criminal Acts As An Effort To Restore The Environment Due To Environmental Crimes By Corporations - Alika Asmir; Mahrus Ali (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
This research entitled "The execution of additional sanctions in the form of repair due to criminal acts as an effort to restore the environment due to environmental crimes by corporations" contains 2 (two) problem formulations, namely (1) What considerations does the public prosecutor make when filing additional sanctions in the form of repair due to criminal acts in a demand letter? (2) How is the implementation of the execution of additional sanctions in the form of repair due to criminal acts ? This research uses empirical legal research methods with normative juridical aspects. The data used is primary data using direct interviews and secondary data through literature studies which are then analyzed descriptively qualitatively with research subjects, namely a Prosecutor at the Prosecutors Office of the Republic of Indonesia. The results of the research show that prosecutors consider additional sanction in the form of repair due to criminal acts important to overcome environmental crimes and support sustainable development, because it directly addresses environmental damage. In contrast, corporate fines are not effective for environmental restoration. The execution of additional punishment in the form of repair due to criminal acts is often not optimal due to the lack of guideline regulation, the absence of time limits and coercive nature as well as the conversion of additional sanctions in the form of repair due to criminal acts into a sum of money.